THE COMPARATIVE ANALYSIS OF GUY DE MAUPASSANT’S TWO FRIENDS AND ARTURO ARIAS’ TOWARD PATZUN - Indriyanto, Kristiawan (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2019)
This paper compares and contrasts two short stories, Guy De Maupassant’s Two Friends and Arturo Arias’ Toward Patzun. Both stories have the same thematic structure as the harshness and brutality during wartime situation is a similar concern to the aforementioned writers. Although both writers foreground the savagery of war, the different cultural background, nationality, literary tradition cause differences in the way both writer narrate their short stories. While De Maupassant depicts the Franco-Prussian War (1870-1871), Arias squares his narration in the Guatemalan civil war (1960-1996). The differences of canonical status between De Maupassant and Arias is also scrutinized in this paper. While De Maupassant is a household name in Western literary tradition, the popularity of Arias remains obscure. This paper argues that the differences in canonization is linked also with the status of Two Friends in the hypercanon, on the other hand Toward Patzun is located in the countercanon. It is hoped that this paper can contribute toward questioning the privileged status of Western literary works compared to the non-Western author.